2022
DOI: 10.1155/2022/9964689
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein (a)/Lipoprotein(a)-Induced Oxidative-Inflammatory α7-nAChR/p38 MAPK/IL-6/RhoA-GTP Signaling Axis and M1 Macrophage Polarization Modulate Inflammation-Associated Development of Coronary Artery Spasm

Abstract: Objective. Apolipoprotein (a)/lipoprotein(a) (Lp(a)), a major carrier of oxidized phospholipids, and α7-nicotinic acetylcholine receptor (α7-nAChR) may play an important role in the development of coronary artery spasm (CAS). In CAS, the association between Lp(a) and the α7-nAChR-modulated inflammatory macrophage polarization and activation and smooth muscle cell dysfunction remains unknown. Methods. We investigated the relevance of Lp(a)/α7-nAChR signaling in patient monocyte-derived macrophages and human cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 173 publications
(233 reference statements)
0
10
0
Order By: Relevance
“…Further, the VAI was associated with chronic inflammation and insulin resistance, due to increases in free fatty acids, interleukin-6, tumor necrosis factor-α, and decreased adiponectin production, related to VAT (23). Inflammatory cytokines and reactive oxygen species lead to decreased nitric oxide concentrations, which are associated with a higher risk of arterial stiffness (24)(25)(26)(27). Additionally, large quantities of fatty acids, due to accumulative visceral adiposity and chronic inflammation, can promote the likelihood of insulin resistance, which is associated with atherosclerosis (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the VAI was associated with chronic inflammation and insulin resistance, due to increases in free fatty acids, interleukin-6, tumor necrosis factor-α, and decreased adiponectin production, related to VAT (23). Inflammatory cytokines and reactive oxygen species lead to decreased nitric oxide concentrations, which are associated with a higher risk of arterial stiffness (24)(25)(26)(27). Additionally, large quantities of fatty acids, due to accumulative visceral adiposity and chronic inflammation, can promote the likelihood of insulin resistance, which is associated with atherosclerosis (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular immune metabolism may be an important factor in the regulation of macrophage polarization (36). It has also been reported that M1 polarized macrophages promote inflammation by producing the pro-inflammatory factor, IL-6 (37,38). Immune cells present in the inflammatory tumor microenvironment may be key to promoting cancer development (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…20 Increased cytokine levels from neutrophils and macrophages, such as IL-6, can enhance coronary contractions by activating Rho-associated kinase. 21,22 In addition, IL-1 induces the synthesis of inflammatory mediators, prostacyclin, and platelet-activating factor, which directly induce CAS. 6,23 Hypersensitivity has been recognized to be related to VSA, which is referred to as Kounis syndrome.…”
Section: Discussionmentioning
confidence: 99%